Postoperative radioiodine therapy impact on survival in poorly differentiated thyroid carcinoma: a population-based study. Issue 2 (February 2022) - Xu, Lei; Zou, Qiong; Jiao, Ju; Zhang, Yong
Abstract : Purpose: The true impact of postoperative radioiodine therapy on survival has been controversial for patients with poorly differentiated thyroid carcinoma (PDTC). We aimed to determine the impact of postoperative radioiodine on survival in PDTC through a population-based study. Methods: Data on patients with PDTC were collected from the US SEER database (2004 to 2015). Patients were divided into the radioiodine group and nonradioiodine group. Survival comparison between groups was evaluated by Kaplan–Meier curves, log-rank test and multivariate Cox regression analysis. Akaike information criterion was used to select variables in the nomogram. The performance of the nomogram was assessed by discrimination (C-index) and calibration plots. Results: The radioiodine group had more aggressive features, such as advanced tumor node metastasis stage and radical surgery, compared to the nonradioiodine group. PDTC patients receiving radioiodine therapy had a significant survival advantage in terms of overall survival (OS) ( P  = 0.001) but not in terms of cancer-specific survival ( P  = 0.083). Multivariate analysis revealed radioiodine therapy was an independent favorable factor for OS in PDTC patients (hazard ratio = 0.57; 95% CI, 0.44–0.75, P  < 0.001). Subgroup analysis identified patients' characteristics favoring radioiodine therapy. The nomogram (age, tumor size, extension, neck lymph nodes metastasis and radioiodine therapy) of OS for predicting 3-, 5- and 10-year OS probability showed good discrimination (C-index, 0.797) and calibration power. Conclusion: Postoperative radioiodine therapy can prolong the long-term OS in patients with PDTC, and is an independent favorable prognostic factor for those patients. Further prospective studies are warranted.